Improving nutrient availability in pyroclastic materials from Mount Kelud using organic and inorganic amendment - Sri Rahayu Utami; Retno Suntari; Christanti Agustina; Novalia Kusumarini (Journal of Degraded and Mining Lands Management, 2019)
Pyroclastic materials from Mount Kelud eruption which deposited in surrounding areas has very low nutrient availability. Fertilizer efficiency is normally low due to a coarse texture. This research was an attempt to increase nutrient availability using zeolite and organic matter in combination with inorganic fertilizers. The materials was treated with three rates of inorganic fertilizers (100%, 70%; 40% of the recommended rates, i.e. Urea 400 kg/ha; SP-36 150 kg/ha, and KCl 75 kg/ha), in combination with three types of amendments (zeolite, Tithonia diversifolia leaves, and cow manure at the rate of 20 t/ha), and 100% inorganic fertilizer treated materials as control, and incubated for 60 days. Soil samples were taken every 10 days after incubation and analysed for soil pH, C-organic, available N, P, K content measurement. The results showed that total N content increased with the rates of inorganic fertilizers. At 10-20 days after incubation the content of NH4+ is greater than NO3- but gradually changed after 30 days after incubation. Apparently, zeolite treated materials had lower NH4+ content than organic treated samples at 10-20 days after incubation, however at 60 days after incubation its NO3- content was relatively higher than Tithonia leaves treated samples. At 60 days after incubation, the higher the fertilizer rates, the higher the content of available P and exchangeable K. The highest content of available P and exchangeable K occurred respectively in cow manure and Tithonia diversifolia leaves treated materials. Until 60 days after incubation, organic treated materials had a higher amount of available and exchangeable K than zeolite treated materials, because they originally contain considerable P and K. However, at 60 days after incubation, zeolite treated materials contained the highest amount of NO3-. This indicated that zeolite had a higher capability to retain mineral N, hindering N removal from leaching and volatilization. A higher nutrient holding capacity could be related to the increasing cation exchange capacity after the addition of amendments, and to a lesser extend to pH and % C.